Comparison of the Oral Hygiene Status in Children With and Without Juvenile Diabetes - A Comparative Study - Lavanya Govindaraju; Deepa Gurunathan (Indian Journal of Dental Research)
Background: The rise in awareness programs with regard to the maintenance of oral hygiene in children with diabetes has led to a hypothetical question if children with juvenile diabetes are still under the risk of developing dental caries and having poor oral hygiene. Aim: To compare the oral hygiene status of the children with and without juvenile diabetes. Materials and Method: The study was conducted as age and sex matched case–control study. Sixty-six children diagnosed with juvenile diabetes were compared with the age and sex matched 66 healthy controls with respect to the oral hygiene index, gingival index and DMFT/def index. Mean of the obtained scores of the variables were compared between the groups using Mann–Whitney test with significance level set at 5%. Results and Conclusion: No statistically significant differences were noted in the gingival condition and dental caries experience between the children with and without juvenile diabetes (P = 0.820; 0.504; 0.422). However, the overall oral hygiene status was found to be poor in children with juvenile diabetes (P = 0.003). No significant differences were observed in the gingival status and the dental caries prevalence between the two groups.